TINJAUAN CEDAW PASAL 11 & 14 DALAM USAHA PEMENUHAN PEMBERDAYAAN PEREMPUAN UNTUK MENGEMBANGKAN UMKM MELALUI LITERASI DIGITAL (STUDI PKK RW 01 RAWA BADAK UTARA): Cedaw Article 11 14 Fulfillment Women's Empowerment Develop Digital Literacy UMKM (PKK RW 01 Rawa Badak Utara) - Safa Maheswari Darastiari; Wahyuni Retnowulandari (Faculty of Law, Universitas Trisakti, 2024)
Efforts to improve gender equality in the long term are possible through the implementation of economic development as described in the Long Term Development Plan (RPJP). The problem in this study is the suitability of articles 11 & 14 of CEDAW in fulfilling the empowerment of women's UMKM in supporting the family economy and what efforts need to be made in encouraging the fulfillment of women's UMKM businesses through Digital Literacy at PKK RW.01 Rawa Badak Utara which aims to find out the problems that occur related to the fulfillment of women's UMKM empowerment in PKK RW.01 Rawa Badak Utara. Socio-Legal approach method. Studies that are interdisciplinary in nature from major studies of legal science and about law from a societal perspective that is born in the daily lives of citizens. The nature of the research used by the author in this research is descriptive analytical research using qualitative juridical methods. Indicate that article 11 & article 14 of CEDAW towards women UMKM PKK RW.01 are in accordance with the fulfillment of women's empowerment in the economic field and the empowerment that has been carried out, is sufficient, it's just that for UMKM through Digital Literacy is still very lacking.